2020
DOI: 10.20473/bikk.v32.1.2020.21-26
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Hemangioma: A Retrospective Study

Abstract: Background: Infantile Hemangioma (IH) is a benign vascular neoplasm and most commonly found in newborns. IH appears in the first few weeks of life and mostly resolve immediately. Early recognition of symptoms, diagnosis, and therapy has an important role in determining the prognosis of this condition. Purpose: The purpose of this study is to evaluate the clinical features of new IH patients in the Pediatric Dermatology Division of the Dermatology & Venereology Department outpatient clinic of Dr. Soetomo Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This value is consistent with the findings of Lydiawati and Zulkarnain, who found that IHs are common in children under the age of 1 year. This condition develops actively during the first few weeks after birth and lasts until it spontaneously involutes around 1 year of age (16).…”
Section: Discussionmentioning
confidence: 99%
“…This value is consistent with the findings of Lydiawati and Zulkarnain, who found that IHs are common in children under the age of 1 year. This condition develops actively during the first few weeks after birth and lasts until it spontaneously involutes around 1 year of age (16).…”
Section: Discussionmentioning
confidence: 99%
“…The most common IH location was the facial region in 49 patients (58.33%). 6 Continuous exploration and optimization of therapeutic regimens have been carried out in recent years for IH. many curative therapeutic regimens have emerged and been applied in clinical practice, including oral medications, injectable medications, topical medications, laser therapy, and surgical treatment.…”
Section: Introductionmentioning
confidence: 99%